Adivinanzas and Dichos: Preparing Prospective Educators to Teach Science by Incorporating Culturally Responsive Tools. Issue 1 (2nd January 2018) - Arreguín-Anderson, María Guadalupe; Ruiz-Escalante, José Agustín
ABSTRACT: Culturally relevant science pedagogy is seldom discussed in terms of infusion of literary resources, such as adivinanzas and dichos in the design of instruction. In this study, the authors narrate how a science methods course was infused with the use of culturally responsive tools to purposefully connect to the elementary science curriculum. Results indicate that prospective Latino teachers found multiple opportunities to address specific science objectives with adivinanzas and expressed the advantages of using these culturally responsive tools to introduce and summarize science concepts as they implemented lessons during field experience.